ANALISIS YURIDIS PERLINDUNGAN HUKUM KONSUMEN TERHADAP PENGGUNA JASA GORIDE DI KOTA PONTIANAK - NIM. A1011181235, YOGA FAJAR NUGRAHA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Land transportation plays a crucial role in the nation's life, as it encompasses all aspects of life. Its fundamental function is to provide road transportation services, whether using motorcycles or other land vehicles, to support the development of other sectors. However, in this case, service providers claim that they are nothing more than technology companies providing applications to connect drivers with consumers. This positioning of the business entity as a party not obligated to assume full and direct responsibility for any potential risks to its customers. Based on the previous brief description, this research was conducted to examine the legal basis for online transportation service consumers, and what responsibilities the company itself has to comply with the law governing consumer legal protection, namely Law No. 8 of 1999 concerning Consumer Protection, then other supporting regulations and policies such as the Regulation of the Minister of Finance, the Regulation of the Minister of Transportation, etc. The results of this research are that PT. Go-Jek as a transportation service provider (Go-Ride) is responsible for providing compensation or insurance, if a consumer who uses its services experiences an accident resulting in death while using Go-Ride, will be given compensation of Rp. 10,000,000.00 and hospital costs of Rp. 5,000,000.00, as a form of responsibility and compensation for consumers who have experienced an accident. The implementation and realization of legal protection for consumer service users is a form of responsibility given by PT. Go-Jek is considered unfair and not in accordance with the Regulation of the Minister of Finance. Keywords : Consumer Legal Protection, Online Transportation Services Abstrak Transportasi darat memiliki peran yang sangat penting didalam kehidupan bangsa, karena semua aspek kehidupan bangsa, tidak ada yang tidak bisa disentuh oleh transportasi. Sesuai dengan fungsi dasarnya, transportasi darat diharuskan untuk menyediakan jasa transportasi jalan, baik menggunakan motor dan kendaraan darat yang lainnya, sehingga mampu mendukung perkembangan sektor